Pemaknaan Santri Mengenai Wacana Poligami Pada Film Surga Yang Tak Dirindukan 2 - Bakhita Aida; Hapsari Dwiningtyas Sulityani (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2018)
The divorce recapitulation data processed by the Religious Courts stated that in 2015 there were 7.476 divorce cases due to polygamy. Polygamy practice developed because polygamy discourse still contains pros and cons or raises perspective in every individual, so to knew the perspective or meaning of the audience on polygamy in the movie of Surga Yang Tak Dirindukan 2, researchers used the method of reception analysis. The purpose of this research was to described the meaning of santri as audiences about polygamy discourse on the movie of Surga Yang Tak Dirindukan 2 .The theory used in this research was the theory of encoding-decoding and Nurture theory. The result of the research showed that there were variations in the meaning of different santri on polygamy discourse on Surga Yang Tak Dirindukan 2. The six informants in the negotiation position justify the permissibility of polygamy with the condition and the special cause. But they were not willing to do polygamy because polygamy makes people feel hurt and polygamy conditions that are difficult to implement that is fair. Where some female santri informants argue that fair includes the established aspects and feelings while the santri son disagrees if the feelings are fair demands. Not only that, some informants agreed that wives who can not perform their duties well are conditions that were allowed to be polygamous. Informant's opinion is based on the textualist's interpretation of Al-Qur’an verses on polygamy, Kitab Kuning, santri and kyai, and the mass media.